Physical - mechanical properties of elastomer diluted with B10 and B20 biodiesel - Hassan, Najmi Aiman (2019)
Nowadays,there are a lot of heavy machineries and vehicles that uses diesel (CI)engine. Therefore,the usage of diesel in industrial application and transportation is increasing rapidly. This type of engines uses diesel as their source of fuel.However, the usage of pure diesel(BO) is very harmful and may pollute the environment due to the release of harmful exhaust gasses and a lot of soot or particulate matter. Therefore,alternative fuel is the best solution for this problem which is biodiesel. This is because the biodiesel tends to produce greener exhaust gasses and less particulate matter that reduce the pollution from the diesel engine.Though the biodiesel and pure diesel share almost the same characteristic, there are a few advantages and disadvantages of biodiesel compared to pure diesel. Biodiesel tends to have the corrosive properties when it is blended with Ultra Low Sulphur Diesel (ULSD). Therefore,usage of biodiesel will affect the elastomer which is one of the main components of the fuel delivery system. The elastomer can usually be found in the fuel lines for diesel engine and also the sealing of the engine parts. In this project, biodiesel B 10 and B20 was studied. Therefore, a few tests have to be done in order to investigate the effect of B 10 and B20 biodiesel on the physical - mechanical properties of the elastomer. For physical test,the mass test before and after soaking in elastomer will be done and.On the other hand, the hardness test and tensile test will be done to test for the mechanical properties of the elastomer before and after soaking in the B10 and B20 biodiesel. However,the elastomer needs to be soaked for a certain amount of time before being tested for the physical - mechanical properties.Each test was done according to the respective ASTM standards which are ASTM 0471 for soaking test and mass test,ASTM 02240 for hardness test,and ASTM D412 for tensile test.